The effect of consumer awareness on food packaging labelling towards purchase intention in Kuala Terengganu / Nur Syafika Najwa Hamsidin and Siti Norashikin Zulkefli - Hamsidin, Nur Syafika Najwa; Zulkefli, Siti Norashikin (2021)
This research proposal is to investigate the consumer awareness on food packaging labelling towards purchase intention in Kuala Terengganu. The purpose of the food packaging labelling study is to emphasize and solve Malaysia's problem, such as the obesity pandemic, leading to more severe illness such as cardiovascular disease, diabetes, stroke, and some cancers. Besides, this is a solution to change the purchase intention of buying towards a health concern person. Furthermore, it can increase the awareness of consumer towards halal issue about the food product either its ingredient and halal label on the food label packaging. Next, the study can solve the problem of the consumer on their perception towards e-nlimber on food label packaging, which known as food addictive code used for food labelling. The study's method will first focus on an individual who is a Malaysian stay in Kuala Terengganu. The population estimated about 384,000 people in 2020. The number of 384 respondents is chosen based on Kuala Terengganu people as a sample (Krejcie & Morgan, 1970). A self-structured questionnaire will be conducted through an online survey distributed through social media. The questionnaire will be in an online form, which requires the participant to fill in the form to complete the survey. The study results will show the frequency of respondents who responded to either the food packaging label study indicates importance or awareness among them based on the question given.